Effects of Chinese herbal medicine on hyperlipidemia and the risk of cardiovascular disease in HIV-infected patients in Taiwan. (12th June 2018) - Tsai, Fuu-Jen; Li, Te-Mao; Cheng, Chi-Fung; Wu, Yang-Chang; Lai, Chih-Ho; Ho, Tsung-Jung; Liu, Xiang; Tsang, Hsinyi; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Li, Ju-Pi; et al.
Abstract: Ethnopharmacological relevance: Due to the development of antiretroviral therapy (ART), HIV/AIDS is now regarded as a treatable chronic disease. Chinese herbal medicine (CHM) is a type of complementary and alternative medicine (CAM) that has been widely applied in the healthcare system in Taiwan. Aim of the study: The aim of this study was to investigate the frequency of use and patterns of prescription for the CHM-based treatment of HIV-infected patients and to assess the long-term effects of CHM on hyperlipidemia and cardiovascular disease events in these patients. Materials and methods: We identified 21, 846 HIV-infected patients (ICD-9-CM: 042-044, 079, and V08 codes). Of these, 1083 and 2166 patients who used CHM and were non-users, respectively, were matched for age, gender, and ART use before CHM. The chi-squared test, Cox proportional hazard model, Kaplan-Meier method, and the log-rank test were used for comparisons between these two groups. Results: CHM users had a lower risk of hyperlipidemia compared with non-users after adjusting for comorbidities by using a multivariate Cox proportional hazard model ( P  = 0.0011; HR: 0.66, 95% CI: 0.52–0.85). In addition, the CHM users had a lower risk of cardiovascular disease compared with non-users after adjusting for comorbidities ( P  = 0.0004; HR: 0.67, 95% CI: 0.53–0.83). The 10-year cumulative incidences of hyperlipidemia and cardiovascular disease were lower in the CHM group ( P  < 0.0001 for both, log rank test). Among the 12 most commonly used CHMs in these patients, Jia-Wei-Xiao-Yao-San (JWXYS) (46.1%), Ge-Gen-Tang (GGT) (40.6%), and Yin-Qiao-San (YQS) (38.0%) were the most common herbal formulas used. Huang-Qin (HQin) (44.6%), Yan-Hu-Suo (YHS) (40.5%), and Jie-Geng (JG) (39.5%) were the most commonly used single herbs. A CHM network analysis showed that JG was the core CHM in one cluster, and BM, MXSGT, and HQin were important CHMs in that cluster. In the other cluster, YHS was the core CHM, and SYGCT and JWXYS were important CHMs. Conclusion: CHM as adjunctive therapy may reduce hyperlipidemia and the risk for cardiovascular disease in HIV-infected patients. The list of the comprehensive herbal medicines that the patients used might be useful in further scientific investigations or therapeutic interventions for preventing atherosclerosis among HIV-infected patients. Graphical abstract: fx1